Granulomatous perioral dermatitis - Nadezhda V. Krasnova; Geliya G. Gimalieva; Larisa G. Sinitsyna; Tat'yana Y. Misyakova (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
Parents of patient S., born in 2018 applied with complaints of rashes on the skin of her daughter's face, accompanied by itching for a year. Topically used cream methylprednisolone aceponate and methylene blue. Objectively: the pathological process was widespread, localized on the skin of the face. On the skin of the face, congestive hyperemia, multiple miliary pustules, vesicles, already opened in places, covered with serous crusts, multiple pink papules were visualized periorally. When conducting a histological examination of the affected area of the skin of the face, characteristic signs for granulomatous dermatitis were revealed: in the follicles, foci of necrosis, macrophages with an admixture of neutrophilic leukocytes, single eosinophils and giant multinucleated cells. In the deep layers of the dermis, rough, unevenly thickened and in places multidirectional bundles of collagen fibers with signs of necrosis and the presence of giant cell granulomas, as well as numerous giant cell granulomas without necrosis, exocytosis of lymphocytes, which is characteristic of granulomatous dermatitis, were determined. The diagnosis was made: Perioral dermatitis, granulomatous form. We were prescribed a long-term oral administration of an antibiotic of the macrolide group, externally calcineurin blockers, emollients and ointments containing zinc. On the background of the ongoing treatment, the rash resolved. There was a stable remission.